Anti-Tumorigenic Effect of Resveratrol in HepG2 cells Controlled with Cytochrome-c Dependent Cell Death : Resveratrol and Cytochrome-c Dependent Cell Death in HepG2 cells - Becer, Eda; Kıyak, Nadire; Vatansever, Hafize Seda; Kükner, Aysel (Progress in Nutrition, 2022)
Resveratrol is a phytochemical that regarded as potential anticancer agent in liver cancer prevention. It had also been shown that resveratrol has role in preventive of cancer and anti-cancer properties. In this study, we aimed to investigate the effects of resveratrol on cell viability, apoptosis, cellular proliferation, JAK/STAT pathway and epithelial-mesenchymal transition (EMT) in human hepatocellular carcinoma cell (HepG2) line. Cell growth and cytotoxicity were evaluated with MTT assay with different concentration (5, 10, 25, 50, 100 μM) of resveratrol in HepG2 cells. The distribution of FasL, cyt-c, caspase-3, Ki-67, ACTA2, CD133, JAK2, N-cadherin, vimentin and STAT3 in HepG2 cells were analyzed using indirect immunoperoxidase technique. The effective dose and incubation time for inhibition of cell growth in HepG2 cells was determined as 100 μM for 48 hours. Decreased Ki-67 immunureactivity following resveratrol application was significant in HepG2 cells. Increased cytc-c, STAT3, vimentin, N-cadherin and CD133 immunoreactivities were significant between resveratrol applicated HepG2 cells and control group. According to our results, resveratrol induced mitochondria-dependent cell death and suppressed proliferation in HepG2 cells. On the other hand, our results showed that resveratrol stimulated cellular self-protection responses through activation of EMT and STAT3 protein expression in HepG2 cells.